Exploring Carbon Nanotubes in Nanotechnology: Functional Properties, Surface Modifications, and Biomedical Innovations - Madhuri (International Journal of Photochemistry and Photochemical Research, 2025)
Significant progress has been made in nanotechnology in recent years, especially in the creation of sensors with a broad range of uses. Among these, carbon nanotubes (CNTs) are cylindrical structures composed of carbon, with diameters in the nanometer range. CNTs originate from graphite sheets, where the graphite layers resemble a rolled-up, continuous, and robust hexagonal mesh. These hexagons have carbon atoms at their vertices. The fabrication of CNTs typically involves three primary methods: chemical vapor deposition, electric arc discharge, and laser ablation. CNTs exhibit several exceptional properties, including high elasticity, excellent thermal conductivity, low density, and chemical inertness. These attributes have made CNTs highly valuable in various fields, including nanotechnology, electronics, optics, and materials science. In addition to their use in sensing, water treatment, and drug delivery, CNTs can be functionalized to enhance their solubility and biocompatibility. Functionalization allows for the attachment of active molecules, making CNTs suitable for integration into biological systems. By modifying the surface of CNTs, it is possible to adsorb or attach molecules or antigens that can be specifically targeted to desired cell populations for therapeutic or immune recognition purposes. Examining Carbon Nanotubes in Nanotechnology: Applications, Surface Alterations, and Functional Features. Additionally, the antibacterial and antifungal properties of CNTs are discussed.
Keywords: Carbon nanotubes (CNTs); drug delivery; functionalization; medical diagnostics; nanotechnology